2022
DOI: 10.37190/ppmp/157409
|View full text |Cite
|
Sign up to set email alerts
|

New insights into pyrite-hydrogen peroxide interactions during froth flotation: experimental and DFT study

Abstract: Hydrogen peroxide (H2O2) is an efficient depressant for pyrite (FeS2) flotation. However, the depressing mechanism of H2O2 is not fully understood. In this paper, the depressing capacity of H2O2 for pyrite was examined by flotation tests. Results revealed that pyrite flotation could be inhibited by H2O2 at pH 6.4. The pyrite powder in H2O2 solution enhanced the release of O2 from H2O2. However, the O2 concentration in the solution was less than that of H2O2; thus, H2O2 is the major oxidant in the solution. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Most of the published studies, however, focus on the removal of heavy metal cations from aqueous solutions using soil minerals such as montmorillonite and kaolinite [61–65] . Novikau and Lujaniene [65] provided a comprehensive comparison of the sorption capacity against various heavy metal ions for these two minerals.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the published studies, however, focus on the removal of heavy metal cations from aqueous solutions using soil minerals such as montmorillonite and kaolinite [61–65] . Novikau and Lujaniene [65] provided a comprehensive comparison of the sorption capacity against various heavy metal ions for these two minerals.…”
Section: Resultsmentioning
confidence: 99%
“…Advanced ab initio calculation (Q. Cao et al, 2023) is very successful in predicting mineral structure and physical properties. The most important thing is that the whole structure and energy of minerals can be expressed by small molecular clusters, small-scale directional forces, or covalent bonds.…”
Section: Quantum Chemical Calculation Of Alkali Dissolved Quartz By C...mentioning
confidence: 99%
“…(Al-Saedi et al, 2019) and other experimental simulations show that both quartz surface and carboxylate are negatively charged, and carboxylate will be repelled on the quartz surface unless it is a positively charged -COOCa + group that can bridge with the quartz surface. Lipatieva et al (2022) and Cao et al (2018) concluded that KOH solution is often used for highly selective etching of quartz and quartz etching in ternary solutions composed of NH4HF2 + isopropyl alcohol + acetic acid has been investigated (Z. Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen peroxide (H 2 O 2 ) is another efficient pyrite depressant. Cao et al [158] studied the interaction between H 2 O 2 and hydrated pyrite (100) surfaces using DFT calculations. The results showed that the H 2 O 2 molecule is prone to react with the pyrite surface to generate an H 2 O molecule and one S=O bond.…”
Section: Iron Sulfide Mineralsmentioning
confidence: 99%